Fiscal policy in Poland: Growth booster or growth buster? - Jacek Tomkiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
This paper presents major challenges for Poland's fiscal policy and strategic choices which have to be made in the area of economic policy in Poland's nearest future. The space to manoeuvre in Polish fiscal policy is very narrow. The most important constraint is not the formal one (Polish Constitution, budget law, European Stabilization and Growth Pact) but the economic one. Huge budget deficit and growing borrowing needs of public sector can destabilize economy and hamper economic growth. Fiscal adjustment is needed but one has to distinguish between means and ends of economic policy. The most important goal of economic policy is always a long-term economic development.
Keywords: 330; Finanzpolitik; Wirtschaftswachstum; Polen